Principles of Solar Gas Turbines for Electricity Generation - Madhlopa, Amos (Green Energy and Technology,, 2018)
This is the first book dedicated to solar gas turbines, providing fundamental knowledge and state-of-the-art developments in the field. A gas turbine is a heat engine in which a mixture of fuel and air is burned in a chamber that is an integral part of the flow circuit of the working fluid. The burnt gas mixture expands and turns the turbine, which can be connected to a generator for electricity production. Solar gas turbines offer an important alternative to conventional gas turbines driven by non-renewable, polluting fossil fuels such as diesel or natural gas. The book provides a comprehensive overview of the topic as well as numerous illustrations.